1998
DOI: 10.1029/98rs00831
|View full text |Cite
|
Sign up to set email alerts
|

Over‐the‐horizon radar target registration improvement by terrain feature localization

Abstract: Abstract. This paper addresses the problem of over-the-horizon radar (OTHR) target position registration in the presence of ill-defined ionospheric structures. At present, OTHR is subject to frequent position uncertainties due to ionospheric abnormalities, such as tilts and ambiguous multipath propagation modes, that are difficult to model adequately during radar operation. The detection and registration of discrete terrain features in parallel with routine radar operations were studied with the goal of signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This procedure is out of the scope of this paper. The reader is referred to [24][25][26]. In other words, we assume that the pair (y l , z l ) of a reference source and its corresponding OTHR measurement is known.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure is out of the scope of this paper. The reader is referred to [24][25][26]. In other words, we assume that the pair (y l , z l ) of a reference source and its corresponding OTHR measurement is known.…”
Section: Problem Formulationmentioning
confidence: 99%
“…One way to tackle the problem above is using reference sources. The reference sources may include HF beacons or transponders [23,24], terrain features (e.g., coastlines, islands and mountains) [25][26][27][28][29], microwave radars [30], and the position information of cooperating targets, such as airliners equipped with automatic dependent surveillancebroadcast (ADS-B) and ships equipped with automatic identification system (AIS). While using the reference sources in CR, their locations in the ground coordinates are assumed to be known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Weijers et al [16] described CR experiments using HF beacons around the US east coast, which demonstrated that using beacons can significantly improve CR. A 3-year investigation was conducted using the Wide Aperture Research Facility experimental OTHR to determine if terrain features could be used as CR benchmarks [17]. The results showed that terrain features could be used in the same way as beacons.…”
Section: Introductionmentioning
confidence: 99%
“…The received radar echo is severely affected by the ionosphere, so how to form effective features is of crucial important [7]. Furthermore, there are not a definite classification boundary between amplitudes of land/sea clutter in regions with complex topography and geomorphology.…”
Section: Introductionmentioning
confidence: 99%